TRADITIONAL HOMEGARDEN AND ITS TRANSFORMING TREND - Karyono - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2000)
Homegarden is a productive traditional landuse system surrounding the housewhich is usually planted by a mixture of annual and perennial crops. Homegardenplays important role in fulfilling various daily needs of the household. It is adynamic system which can change from time to time following the changes ofbiophysical and social to fulfill the needs of the owner. The changes of structureand function of Homegarden are commonly related to the improvement program,i.e. intensification and commercialization. However, in the improvement programtoo often high productivity has been set only as a sole goal, while the long-termof sustainability has been neglected leading the destructive changes in thefunctioning of Homegarden system. Therefore, improvement program should notbe weighted solely on its economic potential, but should also be considered onits socio-cultural and natural conservation function.Keywords : Sustainable Homegarden system